The seeds of the past and the fruits of tomorrow: the transformations and influences of the time in the cultural traits on the acampamento dos agregados of Rosana, Sao Paulo - Cortez Thomaz, Rosangela Custodio [UNESP]; Moreira Goncalves, Leonardo Giovane [UNESP] (Univ Federal Ceara, Programa Pos-graduacao & Filosofia, 2019)
This paper sought to understand whether there have been changes and influences in cultural traits of the agrarian reform camps of this in contrast with those of the past. To achieve these goals, was held a visitation and four interviews in the Acampamento dos Agregados of Rosana/SP to understand their cultural traits and a bibliographical research and documentation in order to understand the oral reports evidenced. In order to analyze the differences of cultural traits between the present and past, previous reports was present in the database of the future Museu do Assentado and the presence of the leader of the camp during the visit. Thus, it was observed that the cultural traits related to preserving food, eating habits, construction of houses, daily habits and other cultural traits have suffered alteration in function of space-time.
Keywords: Cultural traits; Transformations; Camps; Land reform; The Assentado's Museum